Le facteur Chine dans la politique vietnamienne au début du mandat de Donald Trump - Benoît de Tréglodé (MONDE CHINOIS NOUVELLE ASIE, 2016)
The diplomacy of the Socialist Republic of Vietnam (RSVN) has not positioned itself since the beginning of the presidency of Donald Trump. Vietnam does not want to hurt its ties with Washington. Even in the absence of the TPP, the two States have important economic relationships. But the main concern of Hanoi lies in Washington’s attitude towards the South China Sea. Due to its policy of balance between the great powers, Vietnam has always evaluated the place of the United States in the Asia-Pacific regarding to the future of its relationship with Beijing. Faced with China, with whom Vietnam has a complicated historical relationship; there is still no reason for Hanoi of choosing between Beijing and Washington. Vietnam, cautious, fears above all the too inclusive orientations of its multilateral diplomacy